A Juridical Review of the Legality of Educational Institutions Based on Statutory Regulations - Ujang Cepi Barlian (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
The legality of educational institutions constitutes a fundamental aspect of education governance within a statutory framework. Legal compliance ensures that educational institutions operate in accordance with applicable laws and regulations, thereby guaranteeing legal certainty, accountability, and protection of stakeholders’ rights. This article provides a juridical review of the legality of educational institutions based on statutory regulations, focusing on the normative requirements governing establishment, licensing, accreditation, and supervision. Using a normative juridical research method, this study analyzes statutory provisions, legal doctrines, and relevant legal principles related to education law and administrative law. The findings indicate that statutory regulations play a crucial role in defining the legal status and operational legitimacy of educational institutions. However, challenges such as regulatory overlap, inconsistent implementation, and limited supervision may undermine institutional legality and legal certainty. Therefore, strengthening regulatory harmonization, improving enforcement mechanisms, and enhancing legal awareness among education providers are essential to ensure the lawful and sustainable administration of educational institutions.